The Use of Google Translate by Islamic Education Department Students - Purnama, Yulian (Lafadz Jaya Publisher, 2022)
In these digital eras, a Google Translate cannot be separated from students in learning a foreign language. The practicality of Google Translate as online dictionary has changed the position of manual dictionary. This study was conducted to explore perception of students in Islamic Education Department in using Google Translate in learning English subject. A questionnaire consisted of open-ended and close-ended questions was distributed to 138 students of Islamic Education Department. Then, descriptive qualitative research employed to describe and analyze the data. The result show that students assume Google Translate as a good way to help them translate difficult words, sentences, and paragraphes from English to Bahasa or Bahasa to English. Although the students find several problems especially in the quality of translation, they are confident to overcome the problems with effective ways. Moreover, the positive impacts of Google Translate use is greater that the negative impacts for several considerations.